NMDA receptor is involved in neuroinflammation in intracerebroventricular colchicine-injected rats. (3rd July 2016) - Sil, Susmita; Ghosh, Tusharkanti; Ghosh, Rupsa
Abstract: The neurodegeneration in intracerebroventricular (icv) colchicine injected (ICIR) rats is linked with neuroinflammation. Glutamate excitotoxicity through NMDA receptors is involved with the neuroinflammation in some animal models of Alzheimer Disease (AD), but it has not been explored in ICIR rats. The aim of this study was to investigate the role of NMDA receptors (by blocking it's activity with memantine) in colchicine-induced neuroinflammation and neurodegeneration and impacts on peripheral immune parameters in ICIR rats. Levels of inflammatory markers (IL-1 β, TNF α, ROS, nitrite) in the hippocampus and serum, histopathology of the hippocampus and select peripheral immune parameters were measured 14 and 21-days after icv colchicine injection in rats. These parameters were also measured in rats that received daily per os administration of memantine (20 mg/kg) in both study durations. Neuroinflammation in the hippocampus of ICIR rats was associated with neurodegeneration (chromatolysis, plaque formation), along with changes in inflammatory markers in the serum and alterations in peripheral immune parameters (phagocytic activity of WBC and splenic PMN, cytotoxic activity/leukocyte adhesion inhibition by splenic MNC). Administration of memantine to ICIR rats resulted in mitigation of colchicine-induced inflammation in the hippocampus, inflammatory markers in the serum and neurodegeneration and also led to recovery of the measured immune endpoints; most of these effects were greater with the longer duration of study. Phagocytic activity of WBC and splenic PMN cells appeared to correlate with levels of the measured central inflammatory markers. It appears from the results that neuroinflammation might be linked with the NMDA receptor activity in ICIR rats and that this receptor is involved in the process of progressive neuroinflammation and neurodegeneration in the hippocampus of ICIR and potentially in immunomodulation in these same hosts.